Screen-printed carbon electrodes with macroporous copper film for enhanced amperometric sensing of saccharides - Metelka, Radovan; Vlasáková, Pavlína; Smarzewska, Sylwia; Dariusz, Guziejewski; Vlček, Milan; Sýs, Milan (My University, 2022)
A porous layer of copper was formed on the surface of screen-printed carbon electrodes via the colloidal crystal templating technique. An aqueous suspension of monodisperse polystyrene spheres of 500 nm particle diameter was drop-casted on the carbon tracks printed on the substrate made of alumina ceramic. After evaporation, the electrode was carefully dipped in copper plating solution for a certain time to achieve a sufficient penetration of solution within the polystyrene spheres. The metal was then electrodeposited galvanostatically over the self-assembled colloidal crystal. Finally, the polystyrene template was dissolved in toluene to expose the porous structure of copper deposit. The morphology of porous structures was investigated using scanning electron microscopy. Electroanalytical properties of porous copper film electrodes were evaluated in amperometric detection of selected saccharides, namely glucose, fructose, sucrose, and galactose. Using hydrodynamic amperometry in stirred alkaline solution, a current response at +0.6 V vs. Ag/AgCl was recorded after addition of the selected saccharide. These saccharides could be quantified in two linear ranges (0.2-1.0 µmol L-1 and 4.0-100 µmol L-1) with detection limits of 0.1 µmol L-1 glucose, 0.03 µmol L-1 fructose, and 0.05 µmol L-1 sucrose or galactose. In addition, analytical performance of porous copper electrodes was ascertained and compared to that of copper film screen-printed carbon electrodes, prepared ex-situ by the galvanostatic deposition of metal in the plating solution. After calculating the current densities with respect to the geometric area of working electrodes, the porous electrodes exhibited much higher sensitivity to changes in concentration of analytes, presumably due to the larger surface of the porous copper deposit. In the future, they could be incorporated in detectors of flow injection systems due to their long-term mechanical stability.
Sítotiskové uhlíkové elektrody s makroporézním měděným filmem pro vylepšené amperometrické snímání sacharidů
Keywords: non-enzymatic sensors; colloidal crystal templating; porous copper electrodes; amperometric detection; sensing of saccharides; ne-enzymatické senzory; šablonování koloidních krystalů; porézní měděné elektrody; amperometrická detekce; vnímání sacharidů